On photokinetics under polychromatic light - Maafi, Mounir (Frontiers in Chemistry, 2024)
Since the dawn of photochemistry 150-years ago, photoreactions have been conducted under polychromatic light. However, and despite the pivotal role that photokinetics should naturally play for such reactive photosystems, the literature, remarkably, lacks a comprehensive description of that area. Indeed, one fails to identify explicit model integrated rate-laws for these reactions, a characteristic type for their kinetic behaviour, or their kinetic order. Also, there is no consensus in the community on standardised investigative tools to evaluate the reactivity of these photosystems, or even discussion venues of such photokinetic issues. The present work is a contribution addressing some of these gaps in the knowledge. It proposes an unprecedented general formula, capable of mapping out the kinetic traces of photoreactions under polychromatic light irradiation. A study of several reaction situations, including the effects of initial reactant concentration, the presence of spectator molecules, together with developing a methodology for standardising actinometers, a definition of both the spectral range of highest reactivity, and the photonic yield, have been quantitatively described. The validity of the model equation has been proven by comparing its results to both theoretical counterparts, and those generated by fourth-order Runge-Kutta numerical calculations. For the first time, a confirmation of the Φ-order character of the kinetics under polychromatic light was established.